Feasibility and Potential Effectiveness of a Smartphone Zero-Time Exercise Intervention for Promoting Physical Activity and Fitness in Patients With Coronary Heart Disease: A Pilot Randomized Controlled Trial - Chan, Noel P. T.; Lai, Agnes Y. K.; Choy, Hau K.; Cheung, Derek Y. T.; Wan, Alice N. T.; Cheng, Victor Y. H.; Chan, Ka Y.; Lau, Yuk K.; Yung, Chi Y.; Cheung, George O. C.; Lam, T. H. (Frontiers in Public Health, 2022)
Background: Zero-time Exercise (ZTEx), a simple strength- and stamina-enhancing physical activity (PA) requiring no extra equipment, can potentially increase PA and fitness. This pilot trial examined the feasibility and potential effectiveness of a smartphone ZTEx intervention to promote PA and fitness in patients with coronary heart disease (CHD). Methods: A parallel-group assessor-blinded pilot randomised controlled trial was conducted on Chinese patients with stable coronary heart disease (CHD) in three cardiology clinics. The experimental group received a 15-min brief individual face-to-face session and a 12-week ZTEx instant messaging with 28 picture e-messages and a smartphone ZTEx application (ZTExApp). The control group received the same duration of individual session and number and format of e-messages, but the content was healthy eating and breathing exercise. The feasibility was assessed based on: attrition rate, the usage, response rate and perception of the intervention. The outcome evaluation included PA (primary outcome), fitness, exercise self-efficacy and intention, perceived happiness and health, and quality of life. A linear mixed model was used with intention-to-treat analysis adjusting for sex, age and baseline values. A semi-structured interview was conducted to collect feedback from the experiment group. Results: 139 patients (mean age 59.8±6.6; 71.2% male) were randomized to the experimental group (n=70) or control group (n=69), and 80% (56/70) and 82% (57/69) of patients completed the 12-week follow-up assessment, respectively. The attrition rate was 18.7%. The experimental group reported that ZTEx was feasible to integrate PA into their daily life and appreciated the picture e-messages, and 95% of them sent feedback to us, but only 19.6% (13/70) entered their PA information into the e-diary of the ZTExApp. The experimental group had a significantly greater increase in time spent walking [mean difference (95% CI): 155.3 (10.1, 300.4), P=0.04, Cohen’s d=0.34] than the control group. Conclusions: This pilot study showed using a brief ZTEx face-to-face session with picture e-messages empowered patients with CHD to integrate PA into daily life. Future definitive trials with a longer follow-up and a more user-friendly ZTExApp interface are necessary to determine the effectiveness of the smartphone ZTEx intervention in enhancing PA and related outcomes.